Crystal structure of a 1:1 co-crystal of quabodepistat (OPC-167832) with 2,5-dihydroxybenzoic acid using microcrystal electron diffraction - Nasa Sakamoto; Katsuhiko Gato (Acta Crystallographica Section E: Crystallographic Communications, 2023)
Quabodepistat [(5-{[(3R,4R)-1-(4-chloro-2,6-difluorophenyl)-3,4-dihydroxypiperidin-4-yl]methoxy}-8-fluoro-3,4-dihydroquinolin-2(1H)-one); C21H20ClF3N2O4] and 2,5-dihydroxybenzoic acid (2,5DHBA; C7H6O4) were successfully co-crystallized. Given the small size of the crystals (1 × 0.2 × 0.2 µm) the structure was solved via microcrystal electron diffraction (MicroED). The C—O and C=O bond-length ratio of the carboxylic group in 2,5DHBA is 1.08 (1.34 Å/1.24 Å), suggesting that 2,5DHBA remains protonated. Therefore, the material is a co-crystal rather than a salt. The amide group of quabodepistat participates in a cyclic hydrogen bond with the carboxylic group of the 2,5DHBA. Additional hydrogen bonds involving the quabodepistat amide and hydroxyl groups result in a three-dimensional network.